Modern Outlooks on «Atopic March» Secondary Prevention Capabilities in Children with Atopic Dermatitis - Nikolay N. Murashkin; Leyla S. Namazova-Baranova; Roman A. Ivanov; Dmitri V. Fedorov; Eduard T. Ambarchian; Alena A. Savelova; Roman V. Epishev; Alexander I. Materikin; Leonid A. Opryatin (Вопросы современной педиатрии)
Atopic dermatitis (AD) is one of the most common inflammatory diseases of childhood, and it is the first one in gradual development of allergic diseases, also known as «atopic march». Sensitization establishment during the AD uncontrolled course is associated with the high risk of developing of serious allergic pathologies, increase in the severity of the disease course, and patients’ quality of life reduction. Thereby, it is crucial to achieve quick jugulation of the inflammatory process in case of severe AD with early onset of disease. This article shows modern therapeutic approaches to disease control in children.